2015
DOI: 10.1089/gtmb.2015.0019
|View full text |Cite
|
Sign up to set email alerts
|

Screening of GJB6 Gene Large Deletions Among Syrians with Congenital Hearing Impairment

Abstract: Our study reports the first case in Syria with the del(GJB6-D13S1830) mutation. This mutation might be considered in the diagnosis and genetic counseling of inherited hearing impairment in the Syrian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…GJB6 is a gap junction protein, which facilitates the movement of molecules 149 . Mutations in GJB6 are associated with difficulty with CVDs 149,150 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GJB6 is a gap junction protein, which facilitates the movement of molecules 149 . Mutations in GJB6 are associated with difficulty with CVDs 149,150 .…”
Section: Resultsmentioning
confidence: 99%
“…149 Mutations in GJB6 are associated with difficulty with CVDs. 149,150 We mapped a total of 167 mutations onto the GJB6 sequence (Figure 7K). There is one missense, 78 introns, 34 5′ flank, 51 3′ flank, one 5′ UTR and two 3′ UTR mutations.…”
Section: Gjb6mentioning
confidence: 99%
See 1 more Smart Citation
“…There also appears to be notable differences in the frequency of the del(GJB6‐D13S1830) deletion, as depicted in studies in different populations. Although the frequency of the del(GJB6‐D13S1830) deletion in Brazil, France, Czechia, Russia, and Argentina is high (Bliznets et al, ; Dalamón et al, ; Marlin et al, ; Piatto, Bertollo, Sartorato, & Maniglia, ; Seeman et al, ), it is rare or infrequently observed in Austria and Morocco and Syria (Abidi et al, ; Frei et al, ; Gazzaz et al, ; Zaidieh, Habbal, & Monem, ). In contrast, the GJB6 deletion was not identified in many regions including India, Taiwan, Cameroon, Sicily, Mexico, Iran, Macedonia, and Turkey (Adhikary et al, ; Amorini et al, ; Bhalla, Sharma, Khandelwal, Panda, & Khular, , ; Bosch et al, ; Esmaeili, Bonyandi, & Nejadkazem, ; Hernandez‐Juarez et al, ; Naddafnia, Noormohammadi, Irani, & Salahshoorifar, ; Sirmaci, Akcayoz‐Duman, & Tekin, ; Sukarova Stefanovska, Cakar, Filipce, & Plaseska Karanfilska, ; Wonkam et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%